The Influence of Motivation, Training and Communication on the Performance of PT Kereta Api Commuter Indonesia Employees at Tangerang Station - Almajah, Siti Nur; Samsuri; Yuningsih, Erni (MultiTech Publisher, 2024)
The basic principles of management are a decision-making process related to planning, organizing, directing and monitoring to achieve organizational goals. The aim of this research is to determine the effect of motivation, training and communication on the performance of PT Kereta Api Commuter Indonesia employees at Tangerang Station. The sample taken in this study was 60 people using non-probability sampling with a saturated sampling technique. Quantitative descriptive and verification are the analytical methods used in this research. Data collection techniques through questionnaires, observation, interviews and literature study. This research uses multiple linear regression data analysis. The results of this research are that motivation, training and communication have a positive and significant effect on employee performance both simultaneously and partially. The most dominant factor influencing employee performance at PT Kereta Api Commuter Indonesia at Tangerang Station is motivation. Therefore, companies must pay more attention to factors that can increase employee motivation.